The impact of the 'Refugee Problem' and the 'West Bengal Land Reform Act' on the social life of North Bengal : In the context of Jagadish Asoar's novel/ উত্তরবঙ্গের সমাজজীবনে ‘উদ্‌বাস্তু সমস্যা’ ও ‘পশ্চিমবঙ্গ ভূমিসংস্কার আইন’-এর অভিঘাত : প্রসঙ্গ জগদীশ আসো (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2025)
After India’s independence, poverty and the refugee crisis became major issues, particularly in North Bengal, where the situation took on a severe form. The primary objective of the framers of the Constitution was to abolish pre-independence feudalism and establish a democratic socialist system. In accordance with constitutional directives, the passing of land reform acts in each state was a significant step. To fulfill this aim, the Zamindari Abolition Act was passed across India in 1953, and the Land Reform Act was enacted in West Bengal in 1955. According to this law, landowners with holdings exceeding 75 bighas would have their surplus land acquired by the state government, which would then redistribute it among poor, landless peasants. Through this legislation, land rights were granted to the landless population of the state. In the process of implementing and enforcing these laws, North Bengal experienced various upheavals, which brought about changes in its socio-economic, political, and cultural spheres. These changes deeply influenced the lives of the Rajbanshi community and other groups in the region. The novels Mor Nam Mujnai and Hatti Bandha Bari by the writer Jagadish Asoar clearly depict these upheavals. In these works, the long transition from the feudal social system of pre-partition North Bengal to the classless democratic social order of the post-partition and land reform era is vividly presented. The instability and social disruptions of this period are portrayed through the lives of various characters. The present essay analyzes the plots and characters of Jagadish Asoar’s novels to highlight the realities of North Bengal’s social life during that time.
Keywords: North Bengal; Rajbanshi; Partition of India; Land Reforms; Land Redistribution; Bargadar Movement; Refugee Problem; Composite Culture